MEKANISME KOPING DAN PRESTASI BELAJAR MAHASISWA YANG IKUT DAN YANG TIDAK IKUT ORGANISASI - 'Abdul Jaliil, Ihsan; Irvana Dewi, Yulia; Wahyuni, Sri (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2020)
A Proper coping mechanisms are needed for students to avoid stress that should be affected by the student is learning achievement. There is a different type of stress between student who join and do not join the organization. This study aims to look at a comparison of coping mechanisms and learning achievements of students who join and do not join the organization. This study uses a comparative research design with a cross-sectional approach. The number of sample of this research were 159 respondents based on inclusion criteria and using a quota sampling technique. The results of research analysis shows that the majority of respondents were women (86.2%), comes from class A 2016 1 (23.3%), and in 4th semester (54.1%). The organization that participated in is BEM Fakultas Keperawatan dan FSI Al-Kautsar (22%) with one term of organization service (45.9%). Majority of the students used maladaptive cope mechanisms (50.3%) and learning achievements showed in good category (82.4%). The result of statistic test of independent t-test got that there is no significant difference of cope mechanisms between students who join in organization and do not join organization with p-value (0.091) > alpha (0.05) and there is a significant difference of learning achievement where the students who join the organization are better than the students who do not join the organization with p-value (0.001) > alpha (0.05). Based on the result of this research is expected to be a motivation for the students to join the organization because it has a good effect on learning achievements.